The effect of fennel (Foeniculum vulgare) on prevention of postpartum dyspareunia in - Zohreh Alipour; Marzeyeh Loripoor; Zarrin Sarhadynejad; Haleh Tajadini (Mashhad University of Medical Sciences, 2022)
Introduction: Dyspareunia is the most common sexual problem in the postpartum period. Considering the composition and properties of fennel (Foeniculum vulgare), there is a probability of its effectiveness in the prevention and treatment of postpartum dyspareunia. The present study was performed aimed to evaluate the effect of fennel on the prevention of postpartum dyspareunia in primiparous women.Methods: This randomized clinical trial study was conducted on 76 primiparous women referred to Rafsanjan Comprehensive Health Service Centers from January 2017 to May 2018. They were randomly selected as available two weeks after delivery and divided into two groups (n=38 in each group) of receiving 500 mg fennel capsules twice a day for 8 weeks and placebo group. Four and eight weeks after the intervention, both groups were examined in terms of dyspareunia by the Marinoff scale. Data were analyzed by SPSS (version 21) and paired-T and Independent t-test and Chi-square test. P<0.05 was considered statistically significant.Results: The mean dyspareunia score 4 weeks after the intervention in fennel and placebo groups was 0.69 ± 0.61, 0.83 ± 0.69, respectively (p= 0.430) and 8 weeks after the intervention was 0.50 ± 0.57 and 0.70 ± 0.65, respectively (p=0.211). The difference between the mean dyspareunia scores 4 and 8 weeks after delivery was statistically significant in the intervention group (p=0.011). This difference was not significant between the two groups.Conclusion: Taking 500 mg fennel capsules twice a day from the second week after delivery has no effect on the prevention of postpartum dyspareunia. Further studies are suggested in this area.